Import multiplier in input - output analysis - Bui, Trinh (Đại học Kinh tế, 2016)
In this research paper, the Keynesian, Leontief’s and Miyazawa’s multiplier concepts are extended in order to decompose the factors that propagate to total import requirements on such variables as domestic intermediate consumption, domestic final consumption, domestic investment and export. From these extended concepts, we are able to quantify the direct and indirect import requirements and determine the decomposition factors that induce total import requirements. Along with domestic output multipliers, policy makers would be able to look into and consider the import multiplier as a key determinant in sectoral economic planning and policy formulation